Blockchain-based distributed EHR fine-grained traceability scheme - Zuobin YING; Yuanping SI; Jianfeng MA; Ximeng LIU (Tongxin xuebao)
Aiming at the key management of electronic health records (EHR) in a distributed system and user identity tracing issues, a distributed EHR fine-grained traceability scheme based on blockchain was proposed.Combining chameleon hash and zero-knowledge proof technology, the registration of nodes on the blockchain and the generation of identity certificates were realized, and the traceability of malicious users on the blockchain was realized.Besides, given the single point of failure problem of key management, the attribute-based encryption scheme of distributed ciphertext strategy was designed to achieve secure and fine-grained data access control, and multiple decryption agency blockchain nodes were set up to jointly distribute the attribute private keys of user nodes.The security analysis shows that the traceable distributed key generation attribute-based encryption algorithm based on the blockchain is adaptively secure under the random oracle model, and through experiments, the feasibility and practicability of the proposed scheme are shown.